Assessment of Farmer-Led Irrigation Development in Ghana - Dittoh, Saa (World Bank, Washington, DC, 2021)
Adequate agricultural production for food and nutrition security as well as better incomes for farmers and rural inhabitants represent key development objectives of many nations, and they are most crucial in Africa. Water is critical in food production, and its use now and in the future is a major determinant of whether the stated objective is achieved. Because of climate change and associated variability, dependence on rainfed food production is risky and unsustainable. There is a need for substantial increase in irrigated production, particularly farmer-led irrigation development (FLID), in Africa and especially in Ghana. This report consists of an assessment of FLID in Ghana as well as of associated business and financing models that can be pursued for its further development.